Qawā'id Fiqhiyyah and Legal Pluralism: Reconstructing Islamic Family Law toward Gender Equality in Indonesia - Ismail Jalili; Abdul Kabir Hussain Solihu (An-Nisa: Journal of Islamic Family Law, 2026)
The relationship between Islamic family law and national law in Indonesia is still an important legal issue, especially in the areas of marriage, inheritance, child custody, and family rights. However, existing studies tend to focus on formal legal reform and legal pluralism without providing a systematic analytical framework for harmonization that is explicitly based on Qawāʾid Fiqhiyyah and oriented towards gender equality. This research fills this gap by formulating and applying an analytical framework based on Qawāʾid Fiqhiyyah to examine how key legal principles can be used to resolve the normative conflict between Islamic family law and Indonesian national law while promoting gender justice. This study uses a qualitative research design with a comparative-analytical approach through document analysis of classical and contemporary Islamic legal sources, Indonesian laws and regulations, important court decisions, and scientific works that have gone through a peer review process, using iterative coding and thematic comparison. This study centers on the basic principles of justice (ʿadl), benefit (maṣlaḥah), prevention of harm (darʾ al-mafāsid), and custom ('urf), which are operationalized as criteria for assessing legal provisions and patterns of interpretation. The findings of the study show, first, that Qawāʾid Fiqhiyyah facilitates a contextual reinterpretation of family law rules so that provisions on marriage guardianship, alimony, and divorce can be harmonized with constitutional guarantees of equality; second, that the principles of maṣlaḥah and the prevention of harm provide a principled basis for courts to prioritize protection from violence and discrimination in childcare and inheritance disputes; and third, that the recognition of the legitimate 'urf opens up space for the integration of Indonesian socio-legal realities into Islamic legal reasoning without abandoning its doctrinal foundation. Theoretically, this study makes a contribution to formulating Qawāʾid Fiqhiyyah not only as a technical rule of fiqh, but as a normative-analytical framework for the harmonization of rights-based law between Islamic family law and national law in the context of modern countries with Muslim populations.